Nilai-Nilai Kearifan Lokal Kesenian Ronggeng Sakabek Arek Di Kenagarian Persiapan Simpang Timbo Abu Kecamatan Talamau Pasaman Barat - Laela Kurniaty Ilyas; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This study aims to reveal the values of local wisdom of Ronggeng Sakabek Arek Art in the Simpang Timbo Abu Preparatory Kenagarian, Talamau District, West Pasaman Regency, by using the theory of local wisdom values and the theory of performing arts. This research employed qualitative research using descriptive analytical methods. The main instrument is the researcher himself with primary and secondary data types. Data collection techniques are library reviews, observation, interviews and documentation. The object of research is the Ronggeng Sakabek Arek Art in the Kenagarian Preparation of “Simpang Timbo Abu”, Talamau District, West Pasaman. It found that the Ronggeng Sakabek Arek Art was performed at three events, namely (a) the values of local wisdom contained in the Ronggeng Arts Youth Event, (1) the religious values in which the time of Ronggeng art was held after Isya Prayers, ( 2) the moral value of love for Ronggeng art by teaching Ronggeng art to the community even though it is not part of the Ronggeng Sakabek Arek art group, (3) ethical and moral values, before the implementation of Ronggeng art first ask permission from Niniak Mamak and other traditional leaders. (b) The values of local wisdom found in the Ronggeng Art Show at the mamasak night, (1) the religious values at which the Ronggeng art is held after the Isya prayer, (2) the social values to entertain and accompany tired working mothers in the kitchen preparing food for the wedding the next day and feeling love for Ronggeng art by means of the Ronggeng players giving opportunities to children and people who are not members of the Ronggeng Sakabek Arek art group to appear on stage. (c) The values of local wisdom contained in the Ronggeng performance at Aghak-aghak or marapulai processions in the Baralek event are social values, namely the number of families participating in delivering marapulai to the house of the dagho child or bride, as well as for the Ronggeng players. They are willing to take the time to accompany “marapulai” to the house of dagho children.